Uniting Behind Universal Health Coverage - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, remarked that the Isay-Shima summit next May is our opportunity to finally act on the unfulfilled promise of Alma Ata, and move rapidly toward universal health coverage, and to prepare ourselves before the next pandemic hits. Accomplishing these twin goals will represent a quantum leap forward in people’s health and economic wellbeing.